#1**+2 **

Please include your question in the body of your post .. not just in the title :/

x-y=5 (1a) becomes x=5+y (1b)

-4x+4y=20 (2a) becomes -x+y=5 becomes x=y-5 (2b)

Put these together and we get

5+y=y-5

That is never going to happen :(

So there are no solutions. Yes it is very sad :((

Melody
Aug 29, 2017

#1**+2 **

Best Answer

Please include your question in the body of your post .. not just in the title :/

x-y=5 (1a) becomes x=5+y (1b)

-4x+4y=20 (2a) becomes -x+y=5 becomes x=y-5 (2b)

Put these together and we get

5+y=y-5

That is never going to happen :(

So there are no solutions. Yes it is very sad :((

Melody
Aug 29, 2017